Spatial correlation of hand, foot and mouth disease [HFMD] based on the meteorological, environment and population factor in Johor Bahru / Mohammad Hafidzul Fikri Yusop - Yusop, Mohammad Hafidzul Fikri (2020)
The prevalence of Hand, Foot and Mouth disease (HFMD) cases in Malaysia is now rising as reported by several sources such as the mass media and Internet. The aim of this study is to analyse the relationship of HFMD cases based on the population density, weather condition and the temperature in Johor Bahru using Geographical Information System (GIS). Three objectives were designed for this study. The first objective was to create geo-referenced database of Johor Bahru. The second objective aimed to locate HFMD cases distribution and produce hotspot analysis in Johor Bahru. The last objective for this study are aimed to identify the relationship between the meteorological factor, population density and environment factor towards the HFMD cases in Johor Bahru. The result indicates that the disease can occur throughout the year, however it reaches peak in March until August, of which is during the dry season. Furthermore, this study identified the most common areas for the prevalence of HFMD cases in Johor Bahru, which is near the area where migration takes place by producing a hot spot and cold spot map where it is showing which area are affected the most by the disease.